Chiral N, N′‐Dioxide‐Zinc(II) Complex‐Catalyzed Asymmetric Aza‐Friedel–Crafts Reaction of Isatin‐Derived Ketimines with Indoles. Issue 19 (5th August 2016) - Zhang, Xiying; Zhang, Jianlin; Lin, Lili; Zheng, Haifeng; Wu, Wangbin; Liu, Xiaohua; Feng, Xiaoming
Abstract: A highly efficient chiral N, N′ ‐dioxide‐zinc(II) complex catalytic system has been developed for the enantioselective aza‐Friedel–Crafts reaction of isatin‐derived ketimines with indoles. A series of enantiomerically enriched 3‐indolyl‐3‐aminooxindoles containing a tetrasubstituted stereocenter were obtained in up to 99% yield with up to 96% ee . Furthermore, control experiments provide a fundamental sight into the mechanism of the reaction. Abstract :